The impact of fluctuations in volume of transported passengers in urban traffic on the performance indicators of routes - Давідіч, Юрій Олександрович; Доля, Олена Євгенівна (Technology audit and production reserves, 2016)
This article discusses the possibility of applying statistical analysis to the operating costs of the enterprise to make the transportation of passengers on city routes, as well as the impact of fluctuations in volume of transported passengers on such costs. The use of modern means of data analysis allows make a quantitative statistical analysis of the main performance indicators of the enterprise on the city routes. The presented method allows analyzing the activity of the enterprise to evaluate enterprise risks when planning their activities. Scenarios forecasting mechanism for changes of the basic operational resources of the enterprise is shown. The authors propose to use established relationships between the volumes of transportation of passengers and the cost of transportation to ensure the quality of strategic planning. The research results can be applied to the transport companies that provide services for passengers on bus routes of the public service in the cities.